Current status of nanotechnology in urology - Goyal, Suresh K.; Bhat, Amilal; Gupta, Harsh (International Journal of Research in Medical Sciences, 2017)
Nanotechnology has been investigated for its applications in medicine. The objective of this review was to summarize the current applications of nanotechnology in Urology. A systematic search of literature was performed and relevant articles were analyzed with specific reference to applications in Urology. Nanotechnology has applications in diagnostic urology like in uroimaging using nanoparticles and nanosensors. It has therapeutic applications in infections, malignancies, genetic disease using targeted drug delivery, gene transfers, nano device-based manipulations etc. Nanotechnology has many applications in Urology. More efforts are required to make these applications practically feasible and affordable.